Didelphys uterus associated with imperforate hymen: A case report (Research, Society and Development, 2025)
Introduction: Müllerian anomalies consist of a series of changes caused by irregularities during embryogenesis, including didelphys uterus, vaginal canal subocclusion, hematometra, and renal agenesis. Objective: The objective of this study is to present a case report on didelphys uterus associated with imperforate hymen.Case Description: A patient presented with hypermenorrhea associated with intense abdominal pain. Subsequently, imaging studies revealed Müllerian anomalies, leading to hematocolpos drainage and resection of an oblique vaginal septum via laparoscopy. Conclusion: Müllerian anomaly is a gynecological condition characterized by various clinical manifestations, including didelphys uterus, which is usually diagnosed after menarche due to the absence of specific symptoms. Follow-up is essential for case evaluation and appropriate medical management for each patient.